Effectiveness of Training Variations in Improving Forehand Smash Ability in Badminton Game - Nikmah Kuswanti; Yuskhil Mushofi; Rubbi Kurniawan; Trinovandhi Setyawan; Shinta Masitho Windriyani (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This study aims to investigate the effectiveness of variations of arm muscle strength training and body flexibility in improving the forehand smash hitting ability of badminton players.